Coral-Associated Actinobacteria: Diversity, Abundance, and Biotechnological Potentials - Mahmoud, Huda M.; Kalendar, Aisha A. (Frontiers in Microbiology, 2016)
Marine Actinobacteria, particularly coral-associated Actinobacteria, have attracted attention recently. In this study, the abundance and diversity of Actinobacteria associated with three types of coral thriving in a thermally stressed coral reef system north of the Arabian Gulf were investigated. Coscinaraea columna, Platygyra daedalea and Porites harrisoni have been found to harbor equivalent numbers of culturable Actinobacteria in their tissues but not in their mucus. However, different culturable actinobacterial communities have been found to be associated with different coral hosts. Differences in the abundance and diversity of Actinobacteria were detected between the mucus and tissue of the same coral host. In addition, temporal and spatial variations in the abundance and diversity of the cultivable actinobacterial communities were detected. In total, 19 different actinobacterial genera, namely Micrococcus, Brachybacterium, Brevibacterium, Streptomyces, Micromonospora, Renibacterium, Nocardia, Microbacterium, Dietzia, Cellulomonas, Ornithinimicrobium, Rhodococcus, Agrococcus, Kineococcus, Dermacoccus, Devriesea, Kocuria, Marmoricola, and Arthrobacter, were isolated from the coral tissue and mucus samples. Furthermore, 82 isolates related to Micromonospora, Brachybacterium, Nocardia, Micrococcus, Arthrobacter, Rhodococcus, and Streptomyces showed antimicrobial activities against representative Gram-positive and/or Gram-negative bacteria. Even though Brevibacterium and Kocuria were the most dominant actinobacterial isolates, they failed to show any antimicrobial activity, whereas less dominant genera, such as Streptomyces, did show antimicrobial activity. Focusing on the diversity of coral-associated Actinobacteria may help to understand how corals thrive under harsh environmental conditions and may lead to the discovery of novel antimicrobial metabolites with potential biotechnological applications.